Implementation of Education for Sustainable Development in Elementary Schools: An Integrative Review of Challenges, Supporting Factors, and Teaching Approaches - Suratmi Suratmi; Laihat; Latisya Ardi Utami; Prita Amelia Yolanda; Fariz Ghazi Sanjaya (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2026)
Education for Sustainable Development (ESD) is an approach to education that aims to prepare future generations with sustainable lifestyles to support the achievement of the Sustainable Development Goals ( SDGs ). This study aims to examine the implementation of ESD in primary schools in various countries, focusing on the challenges teachers face and the factors that influence the success of its implementation. The method used is an integrative review, which collects and analyzes various studies from leading journals, such as BMC Public Health and Environmental Education Research. The articles analyzed include research from countries such as Lithuania, Malaysia, Indonesia, China, Brazil, and others, with publications ranging from 2013 to 2024. The review results show that despite significant efforts to integrate ESD, implementation still needs to be constrained by teachers' need for understanding, gaps between knowledge and practice, and policy barriers. The study concludes that more comprehensive teacher training, strong policy support, and innovative approaches are needed to improve the success of ESD implementation in primary schools. These solutions are expected to support effective and sustainable ESD integration.